2013
DOI: 10.1007/s00404-013-2775-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-intensity focused ultrasound on sexual function in the treatment of uterine fibroids: comparison to conventional myomectomy

Abstract: Sexual function improved on average to some degree after both HIFU and conventional myomectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…There was a report on the effect of USgHIFU on the sexual function for the treatment of uterine fibroids compared to conventional myomectomy [9]. In that article, an improvement of sexual function was observed after both HIFU and conventional myomectomy.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…There was a report on the effect of USgHIFU on the sexual function for the treatment of uterine fibroids compared to conventional myomectomy [9]. In that article, an improvement of sexual function was observed after both HIFU and conventional myomectomy.…”
Section: Discussionmentioning
confidence: 93%
“…HIFU is the latest developed local ablation technique and a non-invasive technique for the treatment of uterine fibroid and adenomyosis. Results from several published reports have shown that USgHIFU ablation is a safe and feasible alternative for the treatment of uterine fibroids [1][2][3] and adenomyosis [4][5][6]. One advantage of HIFU is its non-invasiveness, which is associated with very low morbidity and very rapid recovery, with return to normal activity in 1 day.…”
Section: Introductionmentioning
confidence: 96%
“…140 High-intensity focused ultrasound (HIFU) shrinks fibroids, facilitating recovery from anemia, depression, fatigue, and deep dyspareunia. 135 The performance of a hysterectomy has been associated with an increase in the postoperative FSFI and European Quality of Life Five-Dimension Scale scores in significant fashion compared with preoperative scores. 141 …”
Section: Benign Gynecologic Diseasementioning
confidence: 99%
“…Most randomized controlled trials (RCTs) of fibroid therapies have been performed outside the United States (210), and those performed in the United States for the related problem of heavy menstrual bleeding have faced recruitment challenges (1114). …”
Section: Introductionmentioning
confidence: 99%